Pengaruh Penggunaan Media Aplikasi Perplexsity Berbasis AI Terhadap Keterampilan Menulis Teks Eksplanasi Siswa-Siswi Smp Kelas Vlll - Situmorang, Hot Ria; Siagian, Beslina Afriani; S, Monalisa Frince (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
This research aims to determine the effect of using AI-based Perplexsity application media on the explanatory text writing skills of class VIII students at SMP N 18 Medan. This type of research is Quantitative Experimental Research with a One group Pretest and Posttest design research design. The population in this study was all class VIII students with a total of 30 students determined using cluster sampling technique. The data analysis techniques used are Normality test, Homogeneity test and Hypothesis test. After conducting research for pretest and posttest experiments using AI-based perplexity application media, the average pretest score was 45.55 and the posttest class was 80.00. The pre-test and post-test data prerequisite test results stated that the sample was normally and homogeneously distributed. From the results of hypothesis testing in this research, a "t" test was carried out at a significant level of 5%, namely dk = N1+N2, dk =30+30- 2 = 58. From df 58, a significant level of 5% = 1.667 Ttable was obtained. From the results of the calculations carried out, it can be seen that Tcount > Ttable 12.0859 > 1.667. So the null hypothesis (Ho) is rejected and the hypothesis (Ha) is accepted. Thus, it can be stated that the ability to write explanatory text is influential using AI-based perplexity application media.